Neoliberalisation, state and social classes: the political economy of contemporary Iran - Valadbaygi, Kayhan/KV (2020)
This thesis analyses socio-economic and political transformations in contemporary Iran. The study aims to overcome the shortcomings of the existing International Relations and International Political Economy literature on the country that has sought explanations based upon various unique internal characteristics whereby Iran is disconnected from the wider space of economic, political and cultural globalisation. By reconstructing a historical materialist approach based on the radical social ontology of the philosophy of internal relations, the project situates Iran within the broader process of neoliberal restructuring of the global economy, therefore taking into account external and internal determinants and global and local dynamics. Accordingly, the proposed method of analysis traces the changes in social relations of production and the transformations in the class structure. It further examines the corresponding changes in the state form and the relationality between the process of neoliberalisation and the nuclear program. It argues that the neoliberal reorganisation of production process since the late 1980s has brought about an internationalist capital fraction and a nationalist capital fraction, named the military-bonyad complex, with contesting interests. The process has thus facilitated different competing accumulation strategies, which in turn have resulted in an unstable combined development, called hybrid neoliberalism. It has also generated an intense struggle within the state due to the historical importance of the state in Iran regarding capital accumulation. As well as changing the function and operation of numerous state institutions, this rising crescendo of confrontation has also provided the material bases for the realisation of the liberal/democratic discourse and the reconfiguration of the revolutionary interpretation of Islam, which has aided the two wings of power in their societal struggle for hegemony. Likewise, the foreign policy of the country has been the subject of this struggle whereby the internationalist fraction and the military-bonyad complex have taken different policies regarding the nuclear program. Considering the internal relations existing between geopolitics and capitalism, the former has utilised the nuclear program to expedite the permeation of foreign capital while the latter’s hardline nationalist approach has enabled the further isolation of Iran by provoking a retaliatory Western stance in the form of international sanctions and frequent military threats from certain U.S. governments in the last few decades.